1965
DOI: 10.2134/agronj1965.00021962005700050030x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Carotenoids in Stored Commercial and High‐Carotenoid Yellow Corn, Zea mays L.1

Abstract: Synopsis Significant differences in losses of carotenoids were found between ground and whole corn and between types of corn as affected by time of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It was reported that commercial high-carotenoid yellow maize lines lost about 30-56 % of provitamin A content during long-term storage (Quackenbush 1963;Dua et al 1965). In case of yellow wheat, approximately 20-48 % total provitamin A was lost when stored even at 20°C for 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that commercial high-carotenoid yellow maize lines lost about 30-56 % of provitamin A content during long-term storage (Quackenbush 1963;Dua et al 1965). In case of yellow wheat, approximately 20-48 % total provitamin A was lost when stored even at 20°C for 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of carotenoids in many food crops has been examined and there generally is a loss of carotenoids during storage, especially in staple crops (www.harvestplus.org/). For instance, in studies of commercial high-carotenoid yellow maize lines, it was found that between 30 and 56% of provitamin A carotenoids were lost during long-term storage (Quackenbush, 1963;Dua et al, 1965). Yellow wheat contains significant amounts of carotenoids, but there is a 20-48% loss of both total and provitamin A carotenoids during storage at 20°C (Hidalgo and Brandolini, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Livingston et al (1955) found that during storage of alfalfa-containing mixed feeds, xanthophyll losses were decreased by the addition of ethoxyquin or oils. Dua et al (1965) stated that "xanthophylls generally are thought to be more stable than carotenes," but did not find differences in their relative losses in a storage study on yellow corn, although Quackenbush (1963) had found such differences in stored corn.…”
mentioning
confidence: 99%